Phase-domain model of twelve-phase synchronous machine for EMTP-type simulation. (December 2022) - Gao, Shilin; Tan, Zhendong; Song, Yankan; Chen, Ying; Shen, Chen; Yu, Zhitong
Abstract: The twelve-phase synchronous machines are widely used for the power supply of integrated power systems on board. This paper formulates two phase-domain (PD)-type models of twelve-phase synchronous machines for the simulation of nodal analysis-based electromagnetic transients programs (i.e., EMTP-type simulation). The PD model for the twelve-phase machine is first formulated, which avoids the interface error in the qd0 model. It is well-suitable for the implementation in EMTP-type simulators. To further improve the simulation efficiency of a power system with twelve-phase machines, a constant conductance PD (CC-PD) model is proposed, avoiding the re-factorization of the network conductance matrix at every time-step. Test results demonstrate the accuracy and efficiency of the two proposed PD-type models for the EMTP-type solution. Highlights: The PD and CC-PD models for the twelve-phase machine are formulated. It fills the gap in EMT simulation for power systems with 12-phase machines. The CC-PD model can be adopted in real-time EMT simulations for power systems.